Double μ2-(phenoxido)-bridged dinuclear and polynuclear nickel(II) complexes: Magnetic properties and DNA/protein interaction. (1st January 2019) - Paul, Aparup; Figuerola, Albert; Puschmann, Horst; Manna, Subal Chandra
Graphical abstract: Double μ2 -(phenoxido)-bridged nickel(II) complexes, [Ni2 (HL)2 (pa)2 (H2 O)2 ]·DMF (1 ) and [Ni2 (HL)2 (ppda)(H2 O)2 ]·DMF·H2 O n (2 ) (H2 L = (E)-2-((1-hydroxybutan-2-ylimino)methyl)phenol, pa = 3-phenylacrylate, ppda = p -phenylenediacrylate), have been synthesized and characterized by X-ray single crystal structure determination. Variable temperature magnetic property studies confirm the presence of an overall antiferromagnetic interaction in both complexes. A spectroscopic study reveals that the complexes interact with CT-DNA and the related intrinsic binding constants are 3.9(±0.10) × 10 5 and 3.43(±0.09) × 10 5 M −1 for1 and2, respectively. Spectroscopic results also indicate that the complexes interact with serum albumins via a ground state association process. Abstract: One dinuclear and one 1D polymeric nickel(II) complex, namely [Ni2 (HL)2 (pa)2 (H2 O)2 ]·DMF (1 ) and [Ni2 (HL)2 (ppda)(H2 O)2 ]·DMF·H2 O n (2 ) (H2 L = (E)-2-((1-hydroxybutan-2-ylimino)methyl)phenol, pa = 3-phenylacrylate, ppda = p -phenylenediacrylate) have been synthesized and characterized by X-ray single crystal structure determination. Complex1 is double phenoxo-bridged dinuclear Ni(II) complex, whereas complex2 is a 1D polynuclear chain where double phenoxo-bridged dinuclear units are connected through bridging ppda ligands. The variable temperature magnetic behavior of the complexes was studied using the Hamiltonian H = − JS 1 S 2, S 1 = S 2 = S Ni and confirms the presence of an overall antiferromagnetic interaction in both complexes. Good agreement between the experimental and simulated curves were found using the parameters: g Ni = 2.15, D Ni = 4.0 cm −1 and JNi–Ni = −0.60 cm −1 for1, and g Ni = 2.15, D Ni = 4.8 cm −1 and JNi–Ni = −3 cm −1 for2 . The interactions of the complexes with CT-DNA were investigated using UV–Vis absorption and fluorescence spectroscopic methods and they show that both the complexes interact with CT-DNA. The intrinsic binding constants values for interaction with CT-DNA are 3.9(±0.10) × 10 5 and 3.43(±0.09) × 10 5 M −1 for1 and2, respectively. The interactions of the complexes with bovine serum albumins (BSA) and human serum albumins (HSA) were also studied using electronic absorption and fluorescence spectroscopic techniques and the results show that both complexes interact with the serum albumins via a ground state association process.